Cranial Nerve Palsy and Diplopia in Typhoid Fever: Case Report - Reza Taslimi; Taha Bayat; Behshad Pazooki; Seyed Ali Nabipoorashrafi (Case Reports in Clinical Practice, 2023)
Salmonella typhi is the cause of an acute febrile illness with high morbidity and mortality, especially in countries with poor sanitation. Neurological complications of salmonella are severe and usually under-diagnosed. This article reports an extremely rare case of a woman with typhoid fever with a history of travel and consumption of raw fish. She had no sign of meningitis but developed diplopia and sixth nerve palsy, which was ultimately resolved by antibiotic therapy.